2009
DOI: 10.1007/s11814-009-0237-0
|View full text |Cite
|
Sign up to set email alerts
|

Production of antifungal lipopeptide from Bacillus subtilis in submerged fermentation using shake flask and fermentor

Abstract: Optimization of the production of antifungal lipopeptide, iturin A, by B. subtilis was carried out in submerged cultural fermentation. In a shake-flask experiment, response surface methodology (RSM) was employed to optimize the cultivation conditions of Bacillus subtilis S3 for the enhancement of iturin A production. The optimal conditions for iturin A production obtained from RSM were pH 6.0, 0.93% maltodextrin, 1.11% glucose, 0.72% corn steep powder (C.S.P), 1.5 mM MgSO 4 , 0.75 mM KH 2 PO 4 , rotation speed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 35 publications
2
12
0
Order By: Relevance
“…They have been used as antifoams, sole carbon sources, auxiliary carbon sources, to provide precursors for antibiotic synthesis and to remove the antibiotic from bacterial access and reduce its suppressive effect on antibiotic production [30]. However, it was considered possible that oil might form a thin film on the surface of the medium, decreasing the oxygen dissolution efficiency, which may influence the production of iturin A [35]. Wu et al [19] verified the negative effects on iturin A production after the addition of either palm or soybean oil.…”
Section: Discussionmentioning
confidence: 99%
“…They have been used as antifoams, sole carbon sources, auxiliary carbon sources, to provide precursors for antibiotic synthesis and to remove the antibiotic from bacterial access and reduce its suppressive effect on antibiotic production [30]. However, it was considered possible that oil might form a thin film on the surface of the medium, decreasing the oxygen dissolution efficiency, which may influence the production of iturin A [35]. Wu et al [19] verified the negative effects on iturin A production after the addition of either palm or soybean oil.…”
Section: Discussionmentioning
confidence: 99%
“…al. confirmed that the increase in kLа value favored production of cell biomass, but repressed the production of iturin A [109]. Since the presence of such metabolites is often very desirable in the broth due to their antifungal properties, cultivation should be further optimized with controlling the agitation rate [108].…”
Section: Microorganismmentioning
confidence: 95%
“…Among the three aeration rates studied, the highest sporulation was achieved at the highest aeration rate (V/Vm = 2 L L -1 min -1 ) [67]. The same aeration rate was used for cultivation of B. subtilis and production of Iturin A achieving excellent yields [88]. Another study also emphasized the importance of adequate aeration, claiming that absence of oxygen may result in lysis of sporangia [101].…”
Section: Cultivation Conditionsmentioning
confidence: 99%
“…It is well known that the FFD method can be used to estimate the main effects of factors [17]. It is particularly useful in the initial stages of medium optimization.…”
Section: -1 Fractional Factorial Design (Ffd)mentioning
confidence: 99%